Potential of Aegilops sp. for Improvement of Grain Processing and Nutritional Quality in Wheat (Triticum aestivum) - Kumar, Aman; Kapoor, Payal; Chunduri, Venkatesh; Sharma, Saloni; Garg, Monika (Frontiers in Plant Science, 2019)
Wheat is one of the most important staple crops in the world and good source of calories and nutrition. Its flour and dough have unique physical properties and can be processed to make unique products like bread, cakes, biscuits, pasta, noodles etc., which is not possible from other staple crops. Due to domestication, the genetic variability of the genes coding for different economically important traits in wheat is narrow. This genetic variability can be increased by utilizing its wild relatives. Its closest relative, genus Aegilops can be an important source of new alleles. Aegilops has played a very important role in evolution of tetraploid and hexaploid wheat. It consists of 22 species with C, D, M, N, S, T and U genomes with high allelic diversity relative to wheat. Its utilization for wheat improvement for various abiotic and biotic stresses has been reported by various scientific publications. Here in, for the first time, we review the potential of Aegilops for improvement of processing and nutritional traits in wheat. Among processing quality related gluten proteins; high molecular weight glutenins (HMW GS), being easiest to study have been explored in highest number of accessions or lines i.e. 681 belonging to 13 species and selected ones like Ae. searsii, Ae. geniculata and Ae. longissima have been linked with improved bread making quality of wheat. Gliadins and low molecular weight glutenins (LMW GS) have also been extensively explored for wheat improvement and Ae. umbellulata specific LMW GS have been linked with wheat bread making quality improvement. Aegilops has been explored for seed texture diversity and proteins like puroindolins (Pin) and grain softness proteins (GSP). For nutrition quality improvement, it has been screened for essential micronutrients like Fe, Zn, phytochemicals like carotenoids and dietary fibers like arabinoxylan and β-glucan. Ae. kotschyi and Ae. biuncialis transfer in wheat have been associated with higher Fe, Zn content. In this article we have tried to compile information available on exploration of nutritional and processing quality related traits in Aegilops section and their utilization for wheat improvement by different approaches.